2014
DOI: 10.1016/s2214-109x(14)70315-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between male circumcision and incidence of syphilis in men and women: a prospective study in HIV-1 serodiscordant heterosexual African couples

Abstract: Background Male circumcision is a primary HIV-1 prevention intervention for men. It is uncertain whether male circumcision reduces the risk of syphilis among men and their female partners. Methods Using data from a prospective study among HIV-1 serodiscordant heterosexual couples from Kenya and Uganda, we assessed whether male circumcision was associated with incident syphilis in men and in their female partners. Multivariate Andersen-Gill survival methods were used, adjusted for age, sexual behavior, and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…Further, a study of young conflict-affected people aged 15–29 residing in transit camps in Northern Uganda observed that ever having had an STI was associated with a four-fold increase in HIV risk among young women, but was not significantly associated with HIV risk among young men [55]. Active syphilis and other GUD in conjunction with low prevalence of male circumcision is worrisome and may be a warning sign for a rise in new HIV infections in the aftermath of war [56]. These findings highlight the importance of post-conflict HIV prevention interventions that support access to STI diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a study of young conflict-affected people aged 15–29 residing in transit camps in Northern Uganda observed that ever having had an STI was associated with a four-fold increase in HIV risk among young women, but was not significantly associated with HIV risk among young men [55]. Active syphilis and other GUD in conjunction with low prevalence of male circumcision is worrisome and may be a warning sign for a rise in new HIV infections in the aftermath of war [56]. These findings highlight the importance of post-conflict HIV prevention interventions that support access to STI diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As documented in a critical review, RCTs and other studies have found MC affords protection against Trichomonas vaginalis (50%), Mycoplasma genitalium (40%), Treponema pallidum (syphilis) (33‐50%), chancroid (50%), and genital ulcer disease (50%) . Genital ulcers in uncircumcised men contain a higher prevalence of anaerobic bacteria.…”
Section: Physical Harmmentioning
confidence: 95%
“…298 A large prospective cohort study of 2946 HIV-negative couples found syphilis was 75% lower in the female partners of circumcised men. 284 A prospective study in Kenya by the same authors found that those with circumcised male partners had a 58% lower risk of incident Trichomonas vaginalis compared to women with uncircumcised partner. 302 A recent systematic review of MC and STIs in women identified 9…”
Section: Protection Against Stis In Womenmentioning
confidence: 99%
See 2 more Smart Citations